Electrotherapy in nowadays cardiology - Kozieł, Monika; Przybylska, Katarzyna; Lenarczyk, Radosław; Kalarus, Zbigniew (Przewodnik Lekarza/Guide for GPs, 2012)
Electrotherapy (catheter ablation, implantation of cardioverter-defibrillators and resynchronization therapy) has played an increasingly important role in recent cardiology. Ablation provides damage to a small part of cardiac tissue which is crucial to the initiation of arrhythmia. It is the best way of treatment most of supraventricular arrhythmias such as AVNRT, Wolf, Parkinson and White syndrome, atrial fibrillation and atrial flutter. Prevention of sudden cardiac death is based on implantable cardioverter-defibrillators (ICD). The place of ICD is not only heart failure (HF) due to coronary disease but also nonischemic cardiomyopathies. Resynchronization therapy (CRT) is a significant part of HF treatment. CRT should be considered in patients with low ejection fraction, symptoms of heart failure despite adequate pharmacotherapy and intraventricular conduction disturbances. CRT reduces morbidity, mortality and increases quality of life among patients with chronic heart failure.